Muslim Consumers’ Perceptions of Religious Symbols as an Indicator of Purchasing Decision in Restaurant Products: A Study in East Barito Regency, Central Kalimantan You'r - Muhammad Zainal Arifin; Jelita Jelita; Abdul Khair; Rabiatul Adawiyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The problem addressed in this study is the existence of non-Muslim restaurants displaying Islamic symbols, such as calligraphy, portraits of religious leaders (tuan guru), and other Islamic imagery. This creates the potential for Muslims to unknowingly dine at non-Muslim establishments due to the presence of such symbols. The research employed a qualitative method. The subjects of this study were the owners of restaurants located along the Trans-Kalimantan road in Barito Timur Regency. Data collection methods included observation, interviews, and documentation, while data validation was carried out using source and method triangulation techniques. The findings reveal that residents who intend to dine at these restaurants consider carefully other indicators, such as whether the servers wear cross necklaces or have tattoos, and whether dogs or pigs are present around the premises. The Ministry of Religious Affairs has been unable to take significant action to address this issue due to the absence of technical guidelines, the vast geographical area of Barito Timur Regency, challenges in monitoring, and the lack of funding to provide public awareness initiatives.